1993
DOI: 10.1099/00221287-139-12-3115
|View full text |Cite
|
Sign up to set email alerts
|

Lysine secretion by wild-type Corynebacterium glutamicum triggered by dipeptide uptake

Abstract: In Cuvynebactevium glutamicum peptide uptake increases the internal concentration of amino acids and thus triggers amino acid secretion. The peptide uptake system is stimulated by a factor of two in cells grown on pure peptone medium in comparison to peptone media with additional carbon sources. Uptake depends on the protonmotive force and shows a broad substrate spectrum. Peptide uptake is characterized by a K,,, of about 230 PM and a Ymax of 12 nmol min-' (mg dry wt)-' for the peptide lysyl-alanine (Lys-Ala)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…Dipeptides provide a means to increase the intracellular level of an amino acid, as their entry into the cytoplasm occurs via the peptide uptake systems. The Lys-Ala dipeptide has previously been employed as a means to increase the intracellular levels of Lys in C. glutamicum (31). We found that the ybjE mutant was impaired for growth in MA medium containing Lys-Ala but not in MA medium containing Arg-Ala or the histidinylalanine (His-Ala) dipeptides (Fig.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Dipeptides provide a means to increase the intracellular level of an amino acid, as their entry into the cytoplasm occurs via the peptide uptake systems. The Lys-Ala dipeptide has previously been employed as a means to increase the intracellular levels of Lys in C. glutamicum (31). We found that the ybjE mutant was impaired for growth in MA medium containing Lys-Ala but not in MA medium containing Arg-Ala or the histidinylalanine (His-Ala) dipeptides (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…5), fulfill the genetic criteria expected if its product were to mediate export of Lys. Lys excretion in C. glutamicum is thought to represent an example of limited catabolism as a physiological model that has been proposed to explain the biological need for amino acid export, since Lys export is required during growth in a medium containing lysyl-dipeptides, as C. glutamicum does not have the capacity to catabolize Lys (14,31). Besides export, another way to redress the growth inhibition caused by elevated cytoplasmic content of an amino acid could be via the activation of its corresponding catabolic route.…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of lysine-containing dipeptides by C. glutamicum has been recently studied (10). Similar to Streptococcus cremoris (12,21), uptake of various lysine-and glutamate-containing dipeptides was found to be driven by the membrane potential, according to a secondary mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of lysine, a detailed kinetic mechanism for excretion involving a secondary process has been described (4). On the one hand, isoleucine, like lysine, is not metabolized in C. glutamicum and has thus to be excreted under conditions of growth on peptides (4,10). On the other hand, isoleucine clearly differs from lysine with respect to hydrophobicity and thus to the ability to cross the membrane by diffusion.…”
mentioning
confidence: 99%
“…Instead, specific efflux systems are known in detail for the removal of fermentation products (1) or the removal of heavy metal ions (21), or they are present to expel antibiotics (25) and are thus directly required for the survival or metabolism of the cell. However, as recently shown, C. glutamicum can take up peptides, which become hydrolyzed to their amino acid constituents within the cell (12). As a consequence, the organism then has to deal with the surplus amino acids which cannot be metabolized and remove them in this particular situation.…”
mentioning
confidence: 99%